The Implementation of Knowledge Management to Enhance Performance of the Banana Plantation Team at PT XYZ - Aldivar Cahyo Santoso (Eduvest - Journal of Universal Studies, 2026)
This study final project was a research to design and provide comprehensive knowledge management system in order to enhance performance of banana plantation team at PT XYZ. Results from a recent knowledge assessment showed the team having an average of 67% on current best practices followed by sequential inconsistency in operational efficiency resulting in 8% fruit weight loss similar to organizational expectations of about approximately 90% target. A mixed research methodology (non-parametric) encompassing the APO Knowledge Management Framework, and SECI model, along with the PPT framework to explore people, process, and technological conditions. Qualitative data were collected through semi-structured interviews, observations and questionnaires. The results show a fragmented KMS, uncommon access to knowledge which is dependent mostly on leaders, training work being reactive and pragmatic most of the times, tacit field-oriented good practice not well documented and exchange of peer-to-peer knowledge without systemic support mechanisms. In short: uninterrupted availability of key information about operations rests more in individuals than institutional mechanisms. Following this, an integrated approach combining APO dimensions, SECI processes and PPT components was used to design a holistic KM system based on these findings. The proposed system includes structured socialization process, standardized externalization process, consolidated combination architecture and strengthened internalization mechanism.